2003
DOI: 10.1182/blood-2003-02-0542
|View full text |Cite
|
Sign up to set email alerts
|

Intensive conventional chemotherapy (ACVBP regimen) compared with standard CHOP for poor-prognosis aggressive non-Hodgkin lymphoma

Abstract: We conducted a randomized trial to compare the intensive conventional chemotherapy regimen ACVBP (doxorubicin, cyclophosphamide, vindesine, bleomycin, prednisone) with standard CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) in previously untreated patients with poor-risk aggressive lymphoma. Patients aged 61 to 69 years who had aggressive non-Hodgkin lymphoma with at least one prognostic factor of the age-adjusted international prognostic index (IPI) were included. ACVBP consisted of an indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
172
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(181 citation statements)
references
References 36 publications
3
172
0
6
Order By: Relevance
“…ACVBP improves results over CHOP in comparative trials assessing patients with localised diff use large B-cell lymphoma 8 and patients with more advanced disease. 9 The association of rituximab with ACVBP in patients younger than 60 years with an ageadjusted International Prognostic Index score of 1, as in our trial, seems to improve progression-free survival from 81% at 2 years 22 to 90%.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…ACVBP improves results over CHOP in comparative trials assessing patients with localised diff use large B-cell lymphoma 8 and patients with more advanced disease. 9 The association of rituximab with ACVBP in patients younger than 60 years with an ageadjusted International Prognostic Index score of 1, as in our trial, seems to improve progression-free survival from 81% at 2 years 22 to 90%.…”
Section: Discussionsupporting
confidence: 53%
“…The induction phase is associated with noticeable haematological toxic eff ects, which is why the regimen is only used in patients younger than 60 years. 9 Most patients experience substantial neutropenia between day 9 and day 13 of each cycle, with a substantial proportion (39%) having a febrile episode despite the use of growth factor. However, our trial and previous ones involving the ACVBP regimen 25 have shown that lifethreatening complications related to treatment are uncommon in a population of patients younger than 60 years with good performance status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been made in patients with CNS relapse of aggressive non-Hodgkin lymphoma. 33,34 Recently, Gan et al 35 reported 4 patients who had diffuse large B-cell lymphomas that were complicated by the presence of NL. It is noteworthy that all NL occurred as recurrent disease during or shortly after those patients completed chemotherapy, as observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…IT methotrexate has been most commonly used historically, 12 but evidence of benefit has been equivocal, with no protective benefit observed in 2 large randomized controlled treatment trials of DLBCL. 2,11,[13][14][15] By contrast, the combination of systemic and IT methotrexate has demonstrated effective reduction in CNS recurrence in DLBCL, 16 suggesting that intravenous methotrexate may be primarily responsible for the risk reduction; however, the protective benefit of intravenous high-dose methotrexate without concurrent IT chemotherapy has never been formally evaluated. In the current study, we present what to the best of our knowledge is the first report of high-dose systemic methotrexate combined with standard chemoimmunotherapy to decrease CNS recurrence in high-risk DLBCL patients.…”
mentioning
confidence: 99%